On the enigmatic Heterolacurbs ovalis Roewer, 1912 (Opiliones, Laniatores, Biantidae) - Pérez-González, Abel; Barroso, Aylin Alegre (Zootaxa, 2009)
In the course of conducting a systematic review of the Cuban Stenostygninae (Biantidae), it has been deemed critical to review Heterolacurbs ovalis Roewer, 1912 from Togo. The habitus and the enlarged metatarsus III of males (as shown in Roewer 1912: 185, fig. 42 and 1923: 143, fig. 154) of this species, which is currently placed in the Lacurbsinae, point to a close relationship with the Caribbean Stenostygninae (Pérez-González 2007). The occurrence of taxa with morphological similarities on both sides of the Atlantic Ocean demanded a detailed study of this species, mainly its penis morphology. It needed to be tested whether H. ovalis is in fact a member of an ancestral Gondwanan lineage, or if its morphological similarities with species from the other side of the Atlantic are due to convergence.